1998
DOI: 10.1021/bc980074o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Oligodeoxynucleotides Containing N4-Mercaptoethylcytosine and Their Use in the Preparation of Oligonucleotide−Peptide Conjugates Carrying c-myc Tag-Sequence

Abstract: The preparation and properties of oligodeoxynucleotides containing mercaptoethyl groups at position N-4 of cytosine are described. The resulting thiol-oligodeoxynucleotides were reacted with a maleimido-peptide carrying the c-myc tag-sequence. The peptide-oligonucleotide conjugate is specifically recognized by an anti c-myc monoclonal antibody, thus constituting a labeling system with sensitivity similar to other existing methods of nonradioactive labeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…After immobilization of the oligonucleotide by UV radiation, the samples were incubated with an anti-c-myc monoclonal antibody [28], followed by incubation with a secondary antibody conjugated to horseradish peroxidase, and developed with a chemiluminescent substrate. It is important to remark that the detection limit on the oligonucleotidepeptide conjugates prepared in this work using the stepwise method is similar to the conjugates prepared by postsynthetic conjugation [10]. This confirm the integrity of the peptide during oligonucleotide synthesis and ammonia deprotection.…”
Section: Immunodetection Of Oligonucleotide-peptidesupporting
confidence: 75%
See 2 more Smart Citations
“…After immobilization of the oligonucleotide by UV radiation, the samples were incubated with an anti-c-myc monoclonal antibody [28], followed by incubation with a secondary antibody conjugated to horseradish peroxidase, and developed with a chemiluminescent substrate. It is important to remark that the detection limit on the oligonucleotidepeptide conjugates prepared in this work using the stepwise method is similar to the conjugates prepared by postsynthetic conjugation [10]. This confirm the integrity of the peptide during oligonucleotide synthesis and ammonia deprotection.…”
Section: Immunodetection Of Oligonucleotide-peptidesupporting
confidence: 75%
“…Recently, we described the introduction of epitope peptide sequences into oligonucleotides as nonradioactive labeling system [10]. Specifically, oligonucleotides carrying c-myc tag-sequence were prepared using a postsynthetic conjugation protocol based on the reactivity of the thiol groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting possibility for future research would be the preparation of asymmetric DNA lattices carrying a protected thiol at one site (to bind to a gold surface) and a molecule of interest at the other site. Previous research has demonstrated that it is indeed feasible to obtain DNA conjugates by removing the tbutylthio group of the thiol group and reacting the resulting free thiol with maleimido groups [16].…”
Section: Afm Imaging Of Dna Latticesmentioning
confidence: 99%
“…The N 4 -[(t-butyldithio)ethyl]-2'-deoxycytidine phosphoramidite was prepared as described elsewhere [16]. After the assembly of sequences, ammonia deprotection was performed overnight at 55 ºC.…”
Section: Experimental Partmentioning
confidence: 99%